A Possible Roll-Over Slab Geometry Under the Caroline Plate Imaged by Monte Carlo Finite-Frequency Traveltime Inversion of Teleseismic SS Phases - Fuji, Nobuaki; Jang, Hyoihn; Nakao, Atsushi; Kim, YoungHee; Fernández-Blanco, David; Lee, Sang-Mook; Schroeder, Alexia; Konishi, Kensuke (Frontiers in Earth Science, 2021)
The shape of a subducting slab varies as a function of trench motion. Two end-members of subduction modes are geodynamically possible: roll-back mode underneath neighboring plates and roll-over mode underneath the plate itself. Whereas most of major slabs seem to roll back while the Pacific plate shows a slab piling behavior down to ~1,000 km depth under the Mariana trench, no clear evidence of slab roll-over in nature has been reported so far. Here we show a possible roll-over slab beneath the Caroline microplate, revealed from its three-dimensional seismic velocity structure derived by analyzing teleseismic reverberating SS phases. We suggest that slab roll-over is driven by at least two factors: i) the overall buoyancy and fragility of the Caroline microplate at the surface, induced by a thin hot mantle plume that rises from depths ≥800 km; and ii) the pushing force of the Pacific plate acting on the trailing edge of the Caroline plate.